1988
DOI: 10.1210/jcem-67-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omega-3 Fish Oils on Lipid Metabolism, Glycemic Control, and Blood Pressure in Type II Diabetic Patients*

Abstract: We investigated the effects of omega-3 fish oil (FO) supplementation on lipid metabolism, glycemic control, and blood pressure (BP) in patients with type II diabetes mellitus. In 22 diabetic patients without overt hyperlipidemia, serum triglyceride, total cholesterol, high density lipoprotein (HDL)-cholesterol, HDL2-cholesterol, HDL3-cholesterol, and apolipoprotein A-I (apo A-I) levels did not change during omega-3 FO supplementation for 8 weeks. The mean serum apo B concentration increased significantly [base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(31 citation statements)
references
References 17 publications
2
27
1
Order By: Relevance
“…We found no significant difference for HL by adding FO. Similarly, a study of Kasim et al (1988) showed that no change was observed in the HL activity during the n-3 fish oil supplementation.…”
Section: Discussionmentioning
confidence: 95%
“…We found no significant difference for HL by adding FO. Similarly, a study of Kasim et al (1988) showed that no change was observed in the HL activity during the n-3 fish oil supplementation.…”
Section: Discussionmentioning
confidence: 95%
“…A fasting blood sample was collected from each participant at the end of each treatment period. The w 3 fatty acid supplement provided 35 mg of w 3 fatty acid per kg of body weight per day, similar to levels previously described [27]. Compliance was assessed by pill counts and periodic telephone or personal contact.…”
Section: Methodsmentioning
confidence: 99%
“…The LDL and HDL cholesterol level was not affected; however, the w 3 fatty acid supplementation increased both the fasting and postprandial plasma glucose level. Feeding fish oil capsules to NIDDM patients without hyperlipidaemia does not change the serum triacylglycerol or the total, LDL and HDL cholesterol level [27]. In these studies, NIDDM patients were fed w 3 fatty acids for short periods when the composition of dietary fat intake was not controlled or assessed.…”
Section: : 45-52]mentioning
confidence: 99%
“…Also in patients with type 2 diabetes, blood pressure was largely unaltered by supplementation with n-3 fatty acids (104). However, many of these studies were conducted with inadequate experimental designs and used doses of n-3 fatty acids Ͻ3 g/day, likely too low to show antihypertensive effects (75,81).…”
Section: Hemostasismentioning
confidence: 99%